Lithium difluoro(oxalate)borate for robust passivation of LiNi0.5Mn1.5O4 in lithium-ion batteries - Mun, Junyoung; Lee, Jieun; Hwang, Taejin; Lee, Jeongyeon; Noh, Hana; Choi, Wonchang (ELSEVIER SCIENCE SA, 2015)
In order to improve the electrochemical performance and understand the mechanisms of capacity fading of lithium nickel manganese oxide cathodes (LiNi0.5Mn1.5O4), we examined the electrochemical performance of cathodes using electrolytes in which LiPF6 was partially substituted with lithium bis(oxalate)borate (LiBOB) or lithium difluoro(oxalate)borate (LiFOB). At ambient temperature, the cells employing the electrolyte containing oxalate-type salts exhibited improved cycle performance, and at an elevated temperature of 45 degrees C, incorporation of the LiFOB salt gave rise to superior capacity retention. In contrast, LiBOB exerted detrimental effects on the electrochemical performance of the cathodes. In-depth electrochemical and spectroscopic analyses revealed that the decomposition of the lithium salt influenced the formation of organic and fluoride films and their growth on the cathode surface; this decomposition may also play a crucial role in controlling the surface characteristics of the cathode material in the lithium-ion battery system during high-voltage application. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: LITHIATED LAYERED OXIDE; FLUORINATED ELECTROLYTES; BIS(OXALATO) BORATE; POSITIVE ELECTRODE; SPINEL; CATHODE; FILM; PROGRESS; LIDFOB; LIBOB